Notes: (6) Brimmond Treasure Trove - Cruickshank, James (Proceedings of the Society of Antiquaries of Scotland, 1943)
A hoard of about a hundred coins lying loose under one of the numerous small boulders was discovered on Brimmond Hill. Most of the coins belonged to the reign of King Charles I. The latest is dated 1632, which suggests that the find is associated with the "troubles" arising out of the Covenanting Wars during the years 1639-46. The coins show signs of considerable use and are largely made up of "Turners" of the time of Charles I. There are a few silver coins, also some of the reigns of Queen Elizabeth and Queen Mary, and a number of Dutch and German origin.